2009
DOI: 10.1002/adfm.200900234
|View full text |Cite
|
Sign up to set email alerts
|

The Active‐Core/Active‐Shell Approach: A Strategy to Enhance the Upconversion Luminescence in Lanthanide‐Doped Nanoparticles

Abstract: Nanoparticles of NaGdF4 doped with trivalent erbium (Er3+) and ytterbium (Yb3+) are prepared by a modified thermal decomposition synthesis from trifluoroacetate precursors in 1‐octadecene and oleic acid. The nanoparticles emit visible upconverted luminescence on excitation with near‐infrared light. To minimize quenching of this luminescence by surface defects and surface‐associated ligands, the nanoparticles are coated with a shell of NaGdF4. The intensity of the upconversion luminescence is compared for nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
508
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 706 publications
(531 citation statements)
references
References 41 publications
11
508
0
5
Order By: Relevance
“…4A). Our synthesized NaGdF4: Yb 31 /Er 31 UCNPs had a hexagonal structure that has been reported to show much higher fluorescent efficiency than does a cubic structure (26)(27)(28). Upconversion luminescence was found to be extremely resistant to photobleaching, and no photoblinking occurred.…”
Section: Discussionmentioning
confidence: 92%
“…4A). Our synthesized NaGdF4: Yb 31 /Er 31 UCNPs had a hexagonal structure that has been reported to show much higher fluorescent efficiency than does a cubic structure (26)(27)(28). Upconversion luminescence was found to be extremely resistant to photobleaching, and no photoblinking occurred.…”
Section: Discussionmentioning
confidence: 92%
“…Xie et al 39 and Wang et al 40 reported the synthesis of monodispersed Nd 3þ -sensitized coreÀshell nanoparticles with narrow size distribution and regular morphology using thermal decomposition method. Vetrone et al 41 reported that the nanoparticles coated with a shell of NaGdF 4 could minimize the luminescence quenching caused by the surface defects and surface-associated ligands. They also found that the UCL of the coated nanoparticles was more intense for the core/shell structure.…”
Section: Thermal Decomposition Methodsmentioning
confidence: 99%
“…For example, to absorb more excitation photons at 980 nm, Capobianco and coworkers 39 41 have also been fabricated to enhance the upconversion emission intensities. In these core-shell structured UCNPs, the amount of Yb 3 þ in the active shell needs to be optimized because the Yb 3 þ can also provide a route to transfer the absorbed excitation energy to the surface quenching centers, which weakens the upconversion emission.…”
Section: Figurementioning
confidence: 99%